Cerium promoted ni/mgo catalyst for biogas dry reforming - Tee, Chin Chow (2014)
In the present work, different loadings of cerium promoted Ni/MgO catalyst for the biogas dry reforming reaction was studied. XRD diffraction pattern of fresh 5 wt% Ce-Ni/MgO catalyst showed peaks representing MgO at 2θ = 37.00 and NiO at 42.99, 62.41, 74.84 and 78.79. BET characterization of both fresh 3 wt% and 5 wt% Ce-Ni/MgO catalysts presented that 5 wt% Ce-Ni/MgO catalyst has larger BET specific surface area, pore volume and pore diameter than 3 wt% Ce-Ni/MgO catalyst. From FESEM imaging of 5 wt% Ce-Ni/MgO catalyst, it can be observed that the metallic particles in the catalyst are uniformly distributed. EDX of fresh 5 wt% Ce-Ni/MgO catalyst displayed that only a small amount of carbon is found for the catalyst showing that the catalyst has high carbon removal efficiency. Reaction studies have found that both 3 wt% and 5 wt% Ce-Ni/MgO catalysts gave almost equal rate of formation of product yield (H2 and CO) which is greater than that of unpromoted Ni/MgO catalyst. However, 5 wt% Ce-Ni/MgO catalyst gives a slightly higher conversion than 3wt% Ce-Ni/MgO catalyst indicating that 5 wt% Ce-Ni/MgO is the best performing catalyst. It was then employed for further reaction studies. The increasing temperature results in increase rate of formation of both CO and H2 as well as the rate of CH4 consumption in agreement with Arrhenius principle. CH4 consumption showed the highest activation energy which is 62.59 kJ/kmol